Buriti: uso e gestão pela comunidade ererê, no entorno do parque estadual de Monte Alegre, Pará - Magalhães, Juliana Lopes (Museu Paraense Emílio Goeldi, 2023)
The use of the buriti palm (Mauritia flexuosa) by residents of the Ererê community, located in the surroundings of Monte Alegre State Park, Pará, dates back to previous times and generations, but is currently in greater prominence. This work, through an ethnobotanical approach, studies the way the community relates to the buriti, as a natural resource of common use and economically useful. The process of exploitation of the buriti, carried out directly by about 21 families in Ererê, goes from the displacement to the native buriti grove, to cutting the fruit, transporting it home, processing it at home, and, finally, selling the products derived from the buriti in neighboring communities or in the city of Monte Alegre, especially the puquêcas, portions of pulp that also contain the shell of the fruit. The work with the buriti is marked by family cooperation and, although the extractivists do not have legal ownership over the buriti grove, the resource has been managed without conflicts among the community members, and the limits between the work of different families are the result of tacit agreements, which have been respected. In line with the advance in the number of collectors, given the stimulus provided by R&D projects in the area, and the space conquered by the product in the market, is the initiative to discuss local parameters for the use and management of the buriti by the residents, in order to improve both productivity and the relationships between the extractivists who decided to work collectively. Today, the families of Ererê are dealing with the resource under a new perspective, not only from a family perspective, but also from a community perspective, because the buriti has gradually become important as a source of income for most families in Ererê, directly or indirectly, and this has made it necessary to have a collective discussion about the best ways to deal with this resource, which is of common use.